2022
DOI: 10.1002/glia.24172
|View full text |Cite
|
Sign up to set email alerts
|

Endocannabinoid signaling in brain diseases: Emerging relevance of glial cells

Abstract: The discovery of cannabinoid receptors as the primary molecular targets of psychotropic cannabinoid Δ 9 -tetrahydrocannabinol (Δ 9 -THC) in late 1980s paved the way for investigations on the effects of cannabis-based therapeutics in brain pathology.Ever since, a wealth of results obtained from studies on human tissue samples and animal models have highlighted a promising therapeutic potential of cannabinoids and endocannabinoids in a variety of neurological disorders. However, clinical success has been limited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 262 publications
(423 reference statements)
0
17
0
Order By: Relevance
“…Given the choice of assessing vGlut1 and vGAT boutons, we were unable to confirm the cell types of CB1R-IR + puncta that did not demonstrate co-labeling, and it is likely these non-vGlut1 and non-vGAT puncta represent a variety of cell types such as vGlut2-expressing glutamatergic neurons 54 . Of note, recent studies have also demonstrated the presence of CB1R in non-GABAergic and non-glutamatergic cell types (e.g., astrocytes, dopaminergic neurons) 55 , as well as in a variety of different subcellular organelles (e.g., lysosomes, endosomes, mitochondria) 56 , and future studies should expand into the investigation of subcellular CB1R localization in postmortem human brain samples.…”
Section: Discussionmentioning
confidence: 98%
“…Given the choice of assessing vGlut1 and vGAT boutons, we were unable to confirm the cell types of CB1R-IR + puncta that did not demonstrate co-labeling, and it is likely these non-vGlut1 and non-vGAT puncta represent a variety of cell types such as vGlut2-expressing glutamatergic neurons 54 . Of note, recent studies have also demonstrated the presence of CB1R in non-GABAergic and non-glutamatergic cell types (e.g., astrocytes, dopaminergic neurons) 55 , as well as in a variety of different subcellular organelles (e.g., lysosomes, endosomes, mitochondria) 56 , and future studies should expand into the investigation of subcellular CB1R localization in postmortem human brain samples.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, De Chiara et al uncovered a novel mechanism by which BDNF influences the function of striatal CB1R (De Chiara et al, 2010). In another study, Abd El-Rahman and Fayed (2022) reported improved cognition in D-galactoseinjected ovariectomized rats via CB2R activation modulating the CREB/BDNF signaling pathway. This promoted CREB phosphorylation for the expression of various pro-survival genes such as BDNF and Bcl-2 which later enhanced the expression of both antioxidant enzymes and the antiapoptotic protein and reduced delayed neuronal death.…”
Section: Glial Cell-endocannabinoid-mediated Synaptic Plasticitymentioning
confidence: 96%
“…The first mechanism occurs in the peripheral immune system, where CB2Rs mediate analgesia by modifying the cytokine profile and preventing adverse effects on the CNS. Secondly, CB2Rs present in glial cells and neurons contribute to pain relief [ 173 , 174 ]. Additionally, studies have shown that selective CB2 agonists promote antinociception [ 175 , 176 ].…”
Section: Endocannabinoid System Emerging As a Pharmacotherapy Target ...mentioning
confidence: 99%